Records of chimaeroid fishes (Holocephali: Chimaeriformes) from the Pacific coast of Costa Rica, with the description of a new species of Chimera (Chimaeridae) from the eastern Pacific Ocean - Angulo, Arturo; López, Myrna I.; Bussing, William A.; Murase, Atsunobu (Zootaxa, 2014)
A new species of Chimaera Linnaeus 1758 is described from three specimens collected from off the Pacific coasts of Costa Rica and Peru. Chimaera orientalis n. sp., the first species of the genus described from the eastern Pacific Ocean, is distinguished from its other congeners by a combination of coloration and morphology. Additionally, new records of occurrence for another four species of chimaeroid fishes (Harriotta raleighana (Goode & Bean 1895), Rhinochimaera africana Compagno, Stehmann & Ebert 1990, Hydrolagus colliei Lay & Bennett 1839, and H. macrophthalmus de Buen 1959) previously unknown for the continental shelf of the Pacific coast of Costa Rica and Central America are reported. A key to the eastern Pacific species of the order Chimaeriformes is also presented.